Anachronistic Avant-garde, or the Art of Tadeusz Brzozowski - Bocheński, Tomasz ((Dif)fusions: Relations between Literature and Art in Poland after 1945, 2019)
The author defines an anachronistic avant-garde – a trend characteristic of modern art in Central Europe. An anachronistic avant-garde expresses the coexistence of Western neurosis of innovation and Central European nostalgia for anachronistic values defining identity. The author notices in the paintings, drawings and titles of Tadeusz Brzozowski’s works the hidden dialogue of these two voices of modern art.